Physical oceanography and current meter data from mooring Y4-1 on the Yermak Plateau, Arctic Ocean, July 2022 – June 2023 - Simon F Reifenberg; Wilken-Jon von Appen; Rebecca McPherson; Mario Hoppmann (PANGAEA, 2025)
This dataset contains processed data from the physical oceanography instrumentation (temperature, salinity, pressure, oxygen, ocean currents) on the Y4-1 mooring. This mooring was part of a mooring array (Y1-1, Y2-1, Y3-1, Y4-1, and Y5-1). Y1-1 and Y2-1 were within 1.7 km distance, Y3-1 and Y4-1 were within 1.9 km distance from each other, and the whole array formed a line (ca. 132 km length) approximately perpendicular to the sea ice edge. The moorings were deployed during RV POLARSTERN expedition PS131 (ATWAICE) in July 2022, and the physical-oceanographic instruments were recovered during PS137 (ALOIS) in June 2023. The scientific objective of the mooring array was related to key mechanisms of the rapid Arctic sea ice decline and Arctic Amplification. These include processes affecting heat fluxes in the air-ice-ocean system, ocean mixed-layer halocline coupling, ice melt, and ice edge dynamics in the marginal ice zone. Therefore, the mooring instrumentation targets the expected strong seasonal variability of the upper ocean. Here, we provide the processed data; the raw data are also published in PANGAEA and are linked below. Note that there can be differences in the listed depths for each instrument compared to the raw data submission. For the raw data, the nominal depths were listed; here, we provide the minimum observed depth after processing, assuming it represents a situation without mooring blow-down. In general, the processing comprises the following steps: for each instrument, the measured time series is cut to the time period the sensor was at target depth, i.e., from after the deployment was completed to before the recovery started. Then, each instrument without its own pressure record is assigned a depth by a constant offset to neighboring pressure sensors, based on the mooring drawing. For ADCPs, the (variable) depth record and cell range information are used to create a time-depth matrix indicating the depth of each ADCP cell at each time step. Data above the 99.98% speed percentile are removed. ADCP bins that showed interference with other gear in the mooring (e.g., large buoyancy floats) were excluded manually. Also, data from ensembles with fewer than 30% good samples were removed, and a threshold of 0.1 m/s for the error velocity is applied. The derived ocean current directions are corrected for magnetic declination. Where applicable, practical salinity is calculated from conductivity. Outliers (upper and lower 0.02% percentile) are removed. Temperature values lower than -3 °C and greater than 30 °C are removed directly. For all SBE37 with dissolved oxygen measurements, the first two days of data are discarded to exclude unreliable data from the sensor membrane adjusting to the water pressure. The attached data contain processed measurements from three Seabird SBE37 MicroCATs (at depths: 19 m, 39 m, 262 m, sampling interval 1h), and one upward-looking Teledyne RDI 300 kHz Workhorse ADCP (at depth: 47m; sampling interval 15 min). The ADCP stopped recording on 13 Jun 2023 due to a low battery.